Evaluating the performance of an AGV fleet in an FMS under minimizing part movement and balancing workload rules - Pereira, Alberto Ferreira (2011)
The performance of an FMS with respect to AGV utilization is assessed using a simulation model. AGV fleets of different sizes are evaluated. Under OOM, an assignment rule designed to decrease time in system by minimizing part movements among machine tools, AGV utilization is lower than under WINO, an assignment rule that seeks to balance machine workload. For a given AGV fleet, machine utilization imbalance is more levelled under WINO than OOM, however comparing across the three AGV fleets, the maximum machine imbalance is smoother under OOM than under WINO. AGV utilization consistently decreases as the number of AGVs increases from eight to nine and then to 10. The system performance is adversely affected not only by too many AGVs but also by surplus spots in both inbound and outbound queues placed in front of the machine tools.